Conflicto armado en Colombia : evidencia de su impacto sobre la producción agrícola municipal (2017)
The economic literature indicates a negative correlation between economic growth and violence. This investigation seeks to quantify the effect that the armed conflict has caused on the agricultural sector among different municipalities in Colombia. Using a panel with information on 807 municipalities from 2000 to 2014, the evidence suggests that the armed conflict has reduced the agricultural production and the number of agricultural hectares cultivated in the different municipalities in the Colombian territory.--Tomado del Formato de Documento de Grado.